Viabilidade de uso de um fogão solar para cocção de alimentos com parábola refletora fabricada em compósito que utiliza fibras de Carnaúba e resina Ortoftálica - Souza, Ricardo Fernandes de (2014)
Presents a composite formed by orthophthalic resin and fiber loading of carnauba straw. The fibers were first dried in direct sun exposure and subsequently ground into fodder for the reduction in size. Various formulations of the composite were preliminarily tested by choosing the one presenting the best processability in applying the mold. The composite produced is used for the manufacture of a parabolic surface subsequently coated with mirror segments, flexible plastic, for reflecting the solar rays incident on it. The reflective parable represents the main element of the solar cooker that works with the concentration of sunlight and has dimensions of 1.14 m in diameter and area of 1.0 m². Manufacturing processes and assembly of solar cooker concentration produced are presented. The results of tests for cooking and baking various foods, including rice, pasta, beans, cake, cassava, shrimp, beef, breaded demonstrating the competitiveness of solar cooker studied with other stoves already manufactured and tested in Brazil are presented and in the world. It was also demonstrated the feasibility of the proposed composite for Prototypes manufacture of solar and other structures that do not require great efforts resistance